2013
DOI: 10.1159/000345336
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Plasma <smlcap>D</smlcap>-Dimer Level and Cerebral Infarction Volume in Patients with Nonvalvular Atrial Fibrillation

Abstract: Background: Plasma D-dimer level may reflect the activity of thrombus formation in the left atrium of patients with nonvalvular atrial fibrillation (NVAF). Proper anticoagulation with warfarin dramatically decreases the rate of cerebral embolism, reduces stroke severity and subsequent risk of death, as well as the level of D-dimer in NVAF patients. However, the predictive value of D-dimer level on cerebral embolism severity has not been examined. Thus, the pur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(34 citation statements)
references
References 76 publications
2
30
1
1
Order By: Relevance
“…In addition, multiple studies have shown that D-dimer levels can effectively predict subsequent embolic events in patients with NVAF, even during oral anticoagulant therapy [15,16,17,18,19]. Matsumoto et al [20] demonstrated that the plasma D-dimer level was significantly associated with infarction volume and poor functional outcome in NVAF patients with cardioembolic stroke. However, few studies have evaluated the D-dimer level in hyperthyroid patients with AF.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, multiple studies have shown that D-dimer levels can effectively predict subsequent embolic events in patients with NVAF, even during oral anticoagulant therapy [15,16,17,18,19]. Matsumoto et al [20] demonstrated that the plasma D-dimer level was significantly associated with infarction volume and poor functional outcome in NVAF patients with cardioembolic stroke. However, few studies have evaluated the D-dimer level in hyperthyroid patients with AF.…”
Section: Introductionmentioning
confidence: 99%
“…A study by Matsumoto whose data could not be included found a link between low D-dimer concentrations and a good outcome at discharge. They did not mention the length of stay in the hospital [37]. The discrepancy in individual findings cannot be explained by different measuring points in time.…”
Section: Discussionmentioning
confidence: 93%
“…The expression of vascular endothelial growth factor (VEGF) was correlated with infarct volume and clinical disability (Scandinavian Stroke Scale) [ 22 ]. D -dimer levels at admission were also associated with total infarct volume in patients with acute ischemic stroke and atrial fi brillation [ 23 ]. The excitatory neurotransmitter glutamate was associated with infarct growth [ 24 ].…”
Section: Stroke Severitymentioning
confidence: 99%